Identifying Areas of Error In The Use of Correlative Conjunction by EFL Students at Tadulako University - Syahbana Andini; Nur Sehang Thamrin; Afrillia Anggreni; Rofiqoh Rofiqoh (MASI Mandiri Edukasi, 2026)
This study investigates grammatical errors in the use of correlative conjunctions in EFL students’ academic writing, particularly in maintaining parallel structure and correct word order. The objective of this study is to identify and classify the types of errors made by students in using correlative conjunctions. This research employed a descriptive qualitative method, with data collected from 17 students’ written texts and analyzed using content analysis based on the Surface Strategy Taxonomy proposed by Dulay, Burt, and Krashen, which includes omission, addition, misformation, and misordering. The findings revealed that a total of 16 errors were identified in students’ writings, with misordering errors as the most dominant type, followed by misformation, omission, and addition as the least frequent. These errors mainly occurred because students had difficulty maintaining grammatical parallelism and correctly arranging sentence elements within correlative conjunction structures. The study concludes that although not all students made errors, some still face challenges in applying correct grammatical rules, especially in constructing balanced sentence structures; therefore, greater emphasis on teaching parallel structure and sentence organization is needed to improve students’ writing accuracy.